SYLLABLE STRUCTURE UNIVERSALS AND SECOND LANGUAGE ACQUISITION - Carlisle, Robert S. (International Journal of English Studies, 2001)
The purpose of this paper is to review research in L2 acquisition that has examined the influence of syllable structure universals on the structuring of interlanguage phonology, research that essentially began in the early 1980's. Not all of the researchers conducting these studies claimed to be examining the influence of syllable structure universals; instead, a number of them expressly stated that they were examining the influence oftypological universals, most of which were documented in Greenberg's (1965) seminal research. However, many of Greenberg's implicational statements are completely in accordance with current theoretical descriptions of the syllable; consequently, the L2 research based on the those implicational statements offer evidence for the influence of syllable structure universals on the structuring of interlanguage phonology.The paper begins with a brief description of syllable structure universals, brief because only those syllable structure universals that have inspired corresponding research in L2 acquisition are presented. The presentation also assumes that the syllable has three constituents: the onset, the nucleus, and the coda. Such a division is in accordance with much of the research on the syllable, and dividing the syllable into these three constituents facilitates both the description of the universals and the review the L2 research.